Mikael Agricolan teosten yhdysadjektiivit - Vaittinen, Tanja (Virittäjä, 2007)
Compound adjectives in the works of Mikael Agricola (englanti) 4/2007 (111) COMPOUND ADJECTIVES IN THE WORKS OF MIKAEL AGRICOLA Mikael Agricolas works contain approximately 2,800 compound adjectives, among which there are altogether more than 300 different compound adjective lexemes. While compound adjectives account for roughly the same proportion of all compounds in Agricolas texts as they do in modern written Finnish, there are structural differences between the compound adjectives used by Agricola and those used today. The article examines the morphological structure of Agricolas compound adjectives and analyses the different types of compound adjective used in his works. The first component in Agricolas compound adjectives and compound participles is a noun (e.g. tuli|kivinen brimstone), an adjective (e.g. hyvn|hajullinen aromatic), a numeral (e.g. yksi|kolminainen trinity), an adverb (e.g. ulkon|kullaton unaffected) or a pronoun (e.g. sen|vuotinen of that year). Among all the occurrences of compound adjectives, those starting with a noun comprise the largest group, whereas among the different types of compound adjective, those starting with an adverb account for the largest share. The writer classifies the different types of compound adjective on the basis of their final component. This can be 1) a derivative incorporating the suffix -inen, 2) some other derivative, 3) a participle, or a derivative incorporating the suffix -vainen/-vinen, 4) a superlative or 5) a non-derivative (and non-compound). The most common of these in Agricolas works are the compound adjectives that end in -inen (e.g. rosin|karvainen rose-coloured). This form is also very common in Finnish dialects and in Modern Finnish. Compounds ending with a participle are also common in Agricolas works (e.g. hyvsti|siunattu blessed with Gods mercy, jumalan|pelkv God-fearing). The use of the other types of compound adjective is considerably less common. There are, for instance, a few occurrences incorporating suffixes that were unproductive (e.g. ep|kelvo-llinen unfit, eri|seura-ton impartial, kaikki|valt-ias almighty, selv|kiele-v plain-talking), and there are also instances where the final component of the compound is a superlative (e.g. kaikkein|pyhin holy of holies) or a non-derivative (e.g. koston|ahne vindictive). The article also looks at the way in which the compound adjectives are formed. Compound adjectives ending in -inen have often been explained as being formed by derivation from compound nouns or clauses, but the writers research indicates that Agricolas word formation process was influenced simultaneously by derivation, compounding and borrowing from other languages. For many of his words, Agricolas model was obtained from a foreign language, and he applied this model to compound adjectives that had long existed in Finnish. Besides foreign languages, Agricola also made use of vernacular words to produce such compounds as luoden|kannettu prematurely born infant and mieli|karvas embittered. Tanja Vaittinen